Magnetic noise detection and imaging from a superparamagnetic core-shell particle via an ensemble of nitrogen-vacancy centers in a thin diamond chip - Thitinun Gas-osoth; Kunitaka Hayashi; Dwi Prananto; Toshu An (Applied Physics Express)
We describe a local fluctuating magnetic field detection of Fe _3 O _4 superparamagnetic core–shell particles via relaxometry of an ensemble of NV centers in a diamond. A thin diamond chip enables optical access to the contact position of the magnetic particle through the backside. A significant drop in NV relaxation time near the particle was observed and was evaluated using a model incorporating ensemble NVs and magnetic particles. Additionally, the local magnetization curve (B-H curve) was measured by analyzing ODMR frequency splitting under external magnetic fields aligned with an NV axis. This study expands the NV sensing to applications involving collective superparamagnetic particles.